Activation of C3 and binding to Aspergillus fumigatus conidia and hyphae. - Kozel, T R (1989)
Complement activation by Aspergillus fumigatus may play a crucial role in stimulating binding and killing of this organism by phagocytes. We examined the amount and type of C3 deposited on resting conidia, swollen conidia, and hyphae of A. fumigatus after incubation in pooled human serum. All three life forms of A. fumigatus were potent activators of the complement cascade, with deposition on the organisms of similar amounts of C3 per unit of surface area. The rate of deposition was slowest for resting conidia, although maximal deposition was still achieved within 40 min. The roles of the alternative and classical pathways were assessed by use of serum chelated with magnesium EGTA [magnesium ethylene glycol-bis(beta-aminoethyl ether)-N,N,N',N'-tetraacetic acid] and with an alternative pathway reconstituted from the six purified alternative-pathway proteins. Complement activation by resting conidia was mediated by the alternative pathway. In contrast, there was a progressive dependence on the classical pathway as the fungal particles matured into swollen conidia and then hyphae. Treatment with hydroxylamine, which disrupts ester linkages, removed 89 to 95% of the C3 bound to all three forms of A. fumigatus. This released C3 contained a mixture of C3b and iC3b, as determined by sodium dodecyl sulfate-polyacrylamide gel electrophoresis and autoradiography. These data demonstrate that although all three forms of A. fumigatus are potent activators of the complement system, the transition from resting conidia to swollen conidia to hyphae results in progressive changes in the manner in which the fungal particles interact with the complement system. The lack of participation of the classical pathway in complement activation by resting conidia may have important implications regarding their ability to effectively stimulate phagocytes.